Protocol for metagenomic virus detection in clinical specimens - Kohl, Claudia; Brinkmann, Annika; Dabrowski, Piotr W; Radonić, Aleksandar; Nitsche, Andreas; Kurth, Andreas (Emerging infectious diseases, 2015)
Sixty percent of emerging viruses have a zoonotic origin, making transmission from animals a major threat to public health. Prompt identification and analysis of these pathogens are indispensable to taking action toward prevention and protection of the affected population. We quantifiably compared classical and modern approaches of virus purification and enrichment in theory and experiments. Eventually, we established an unbiased protocol for detection of known and novel emerging viruses from organ tissues (tissue-based universal virus detection for viral metagenomics [TUViD-VM]). The final TUViD-VM protocol was extensively validated by using real-time PCR and next-generation sequencing. We could increase the amount of detectable virus nucleic acids and improved the detection of viruses <75,000-fold compared with other tested approaches. This TUViD-VM protocol can be used in metagenomic and virome studies to increase the likelihood of detecting viruses from any biological source.